Breakthrough Potential in Near-Infrared Spectroscopy: Spectra Simulation. A Review of Recent Developments - Beć, Krzysztof B.; Huck, Christian W. (Frontiers in Chemistry, 2019)
Near-infrared (12,500-4000 cm-1; 800-2500 nm) spectroscopy bears the hallmark of being one of the most rapidly advancing analytical techniques over the last few decades. Although it is mainly recognized as an analytical tool, near-infrared spectroscopy also has a significant contribution to physical chemistry, e.g. by delivering invaluable data on the anharmonic nature of molecular vibrations or peculiarities of intermolecular interactions. In all these contexts one has often encountered a major barrier in the form of an intrinsic complexity of near-infrared spectra. Large number of overlapping vibrational contributions influenced by anharmonic effects create complex patterns of spectral dependencies in many cases hindering our comprehension of near-infrared spectra. Quantum mechanical calculations commonly deliver a major support to infrared and Raman studies; conversely, near-infrared spectroscopy has long been hindered in this regard due to practical limitations. Advances in anharmonic theories in hyphenation with ever-growing computer technology have enabled feasible theoretical near-infrared spectroscopy in the recent time. Accordingly, one has witnessed a growing number of quantum mechanical investigations aimed at near-infrared region. The present review article summarizes these most recent accomplishments in the emerging field. Applications of generalized approaches such as vibrational self-consistent field and vibrational second order perturbation theories as well as their derivatives, and dense grid-based studies of vibrational potential are overviewed. Basic and applied studies are discussed with special attention paid to the ones which aim at improving analytical spectroscopy. A remarkable potential arises from the growing applicability of anharmonic computations to solving the problems which arise in both basic and analytical near-infrared spectroscopy. The review highlights an increased value of quantum mechanical calculations to near-infrared spectroscopy in relation to other kinds of vibrational spectroscopy.